Empowerment of Coastal Communities in the Management of Shell Shell Waste Into Economically Value Products in Tanjung Balai - Meutia Nanda; Aprida Aulia Rizki; Adinda Azima Riskiya Sibarani; Amalia Rahmi; Nuri Nabila Syahputri (Universitas Muhammadiyah Palu, 2024)
Empowerment programs must be implemented in the context of alleviating poverty in coastal communities. A program to empower poor families for coastal communities that can be carried out is by using shell waste to create creative art products because shell waste is a waste that has economic value when made into crafts. This research is a case study research with descriptive research type. This research interviewed several sources such as the local community, craftsmen and distributors or traders of shell crafts. Shellfish shell waste processed and developed by the Tanjung Balai coastal community has sales value so this program is effective in helping improve the community's economy and is effective in reducing environmental pollution. The conclusion from this research is that shellfish have economic value for the coastal communities of Tanjung Balai, making this program effective in helping improve the economy of coastal communities. The suggestion is that there is a role for the government and private sector to develop this product to be better and have a higher selling price.